Increased Angiostatin Levels in Bronchoalveolar Lavage Fluids from ARDS Patients and from Human Volunteers after Lung Instillation of Endotoxin - Lucas, Rudolf; Lijnen, H. Roger; Suffredini, Anthony F.; Pepper, Michael S.; Steinberg, Kenneth P.; Martin, Thomas R.; Pugin, Jérôme (Thrombosis and Haemostasis, 2002)
Acute respiratory distress syndrome (ARDS) is characterized by a disruption of the alveolar-capillary barrier, due to both an epithelial and an endothelial dysfunction. Whereas epithelial apoptosis seems to be mainly mediated by Fas ligand, the mediators of endothelial damage remain to be identified. Angiostatin, a powerful inhibitor of angiogenesis in vivo, also specifically induces apoptosis in endothelial cells. The concentration of various enzymes that cleave angiostatin from plasminogen was reported to be significantly increased in bronchalveolar lavage (BAL) fluids from patients with ARDS. Therefore, in this study, we investigated whether angiostatin was generated during the pulmonary inflammatory response of both healthy subjects challenged with endobronchial endotoxin and in patients with ARDS. We found significantly elevated angiostatin levels in BAL fluids from patients at risk for and with early ARDS (up to 0.022% and 0.018% of total protein, respectively), as well as in BAL fluids from volunteers treated with endotoxin (up to 1.17% of total protein), as compared to BAL fluids from control patients (<0.005% of total protein). These data suggest that angiostatin may contribute to the endothelial damage observed in ARDS, probably via an increased permeability of the alveolar capillary barrier, allowing for an intra-alveolar processing of its precursor plasminogen.
Keywords: Adult respiratory distress syndrome; endothelium; angiostatin; lipopolysaccharide